Psychological Well-Being and Youth Autonomy: Comparative Analysis of Spain and Colombia - Charry, Claudia; Goig, Rosa; Martínez, Isabel (Frontiers in Psychology, 2020)
The construct of autonomy appears in the literature associated with individual psychological wellbeing. In Ryff's model, autonomy is presented as one of the dimensions of wellbeing, along with self-acceptance, positive relationships with others, environmental mastery, purpose in life, and personal growth. The present study compared the levels of autonomy and psychological wellbeing between Spanish and Colombian young people. Ryff's Scale of Psychological Wellbeing and the Transition to Adulthood Autonomy (EDATVA according to its initials in Spanish) scales were used on a sample of 1,146 young people aged between 16 and 21; 506 Spanish and 640 Colombian. Results showed differences in autonomy and in two of the four dimensions proposed by the EDATVA: self-organization and critical thinking. Similarly, important differences were observed in the subscales of positive relations and purpose in life. The importance of contextual factors in the development of psychological well-being and autonomy in young people in transition to adulthood is discussed.